HIV LONG TERMNON DISEASE PROGRESSORS AND HIGHLY EXPOSED PERSISTENTLY SERONEGATIVE POPULATIONS OF WARANGAL, INDIA - RADHAKRISHNA, MUTTINENI; REDDY, M. KRISHNA; KRISHNA, D. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
In India, 4 million people have been infected with AIDS disease. Nearly 1% of the adult population in India is infected with HIV. Extraordinary burden of HIV-related morbidity and mortality lies ahead in India. In Andhra Pradesh about 4–5 Lakh people are infected so far, which accounts 20.60% in STD clinics and above 1% in general population. In Warangal district HIV/ AIDS victimize 40.4% of STD and 6.25% of general population during 2002. Every day 5-10 new HIV cases are recorded on an average in various government & private hospitals in Warangal district. This study identifies HIV highly exposed persistently seronegative and non disease progressors in the south Indian set up. Study design includes Pregnant women and their husbands, sero negative babies who were born to seropositive parents of maternity hospitals, serodiscordent couples of the STD clinic & VCTC center, full blown AIDS patients and their non disease spouses in HIV hospital were studied for their stage of infection and highly exposed but persistently seronegative individuals. During 1996 to March 2006, serodiscordant couples and seropositive patients of various hospitals who returned to collect the report of their blood test for HIV were encouraged to enroll in this prospective study. HIV infection and manifestations were recorded with the help of clinicians. HIV seropositivity was confirmed by three individual tests : (1) HIV TRIDOT, (2) COMB AIDS or EIA (Enzyme immuno assay) and (3) NEVA TEST. Finally sero states are confirmed by Western blot. This study was conducted in maternity, civil and HIV hospitals in and around Warangal, Andhra Pradesh, South India. According to World Health Organization clinical manifestations classification staging system 60 HIV long-term non-disease progressors and highly exposed persistently seronegative subjects were found out of 1021 HIV discordant couples and other positive subjects. These epidemiological results of our investigation suggesting an association between humoral and cellular responses and HLA (human leucocyte antigen) of these highly exposed persistently seronegative subjects and non diseases progressors are very important observation for future epidemic.